Comparative Evaluation of Flexural Strength of Two Newer Composite Resin Materials: An in Vitro Study - Akshata Patil; Shashi Rashmi Acharya; Kishore Ginjupalli (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate in vitro the flexural strength of two newer composite resin materials. Material and Methods: Twenty-four samples were equally divided into two groups: G1 - Brilliant EverGlow and G2: Brilliant NG. The rectangular blocks of 25 mm in length, 2 mm in width and thickness were prepared from two composite materials. Blocks were created by applying composites to a customized split mold and formed between two parallel glass plates. Before light-curing, blocks were covered with Mylar strips and rinsed for 10 seconds in water. Subsequently, they were stored in distilled water for 24 hours at 37ºC and 100% humidity before testing. Each sample was placed within a suitable framework of aluminum. The length of gap between the support was 21 mm and the speed of crosshead at 1 mm/minute. The data were subjected to an independent t-test. The level of significance was set at p <0.05. Results: A less flexural strength was observed in G1 (77.43 Mpa) compared to G2 (118.70 Mpa) (p<0.001). Conclusion: Universal nanohybrid composite resin material was found to have greater flexural strength than universal submicron hybrid composite material.